Pelembab Bibir Lip Balm dengan Memanfaatkan Ekstrak Daun Anggur (Vitis vinifera L.) - Devina Chandra; Steven Tandiono; Manuppak Irianto Tampubolon; Natanael Priltius (STIKes Ibnu Sina Ajibarang, 2023)
Grape leaves (Vitis vinifera L.) contain vitamin E and flavonoids which had the potential to act as a moisturizer by preventing the loss of body fluids from the surface of the skin, so the lips will not dry quickly. This study aims to determine the effectiveness of grape leaf extract in the form of lip balm lip balm that meets quality. Grape leaves are made in the form of thick extracts and formulated into lip balms with various concentrations of 0, 1, 3 and 5%. The results showed that grape leaf extract which was formulated in the form of lip balm preparations had homogeneous properties and different colors for each concentration, the higher the concentration, the light green color became dark green. Lip balm preparations have a melting point value of each formula 56.2-61.0℃; strength test value of 220-300 g; pH test value 5.56-5.94; stable at room temperature for 4 weeks, and does not cause irritation such as erythema, papules and vesicles. The effectiveness of this lip balm preparation was tested using a skin analyzer with a humidity value of 9.43 for each formula; 17.70; 28.95; and 39.93%. The conclusion of this study is that grape leaf extract lip balm has a high level of moisture at a concentration of 5% (F3) and has a significant difference with other formulas.